Pengaruh Lama Perendaman Jeruk Nipis Terhadap Kadar Formalin Pada Cumi Asin - Supriyatin; Pipin Supenah; Solikhah; Indiya Gilang (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Salted squid is a substitution in development. After realizing the importance of these foods as a source of body nutrients, consumption of salted squid has increased. However, there are still many traders who use formalin to preserve salted squid. Some characteristics of salted squid containing formalin are clean, fly-free, and do not rot at room temperature for more than a month. One way to reduce the formalin content in salted squid before cooking can be by soaking it with lime. Because lime contains a lot of organic acids in the form of citric acid. This study was conducted to determine the optimal concentration of lime to reduce formalin levels and see the significant effect of lime concentration on reducing formalin levels in salted squid. The research method used in this study is Pre Experiment with one group pre test post test design. Formalin identification was carried out qualitatively using distillation and the addition of chromatropic acid and quantitatively using a spectrophotometer with a wavelength of 570nm. The formalin level in squid was 0.1682ppm. Samples were treated by soaking with lime juice with a concentration of 20%, 40%, 60%, 80%, 100% with a duration of time of 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, the results showed the highest decrease in formalin levels at a soaking time of 5 hours with a concentration of 100% lime juice.